Effect of turmeric starch, lecithin, and canola oil supplements on waffles quality - THUY, Nguyen Minh; HAO, Hong Van; THU, Le Chau Mong; GIAU, Tran Ngoc; TIEN, Vo Quoc; TAI, Ngo Van; THANH, Nguyen Van (Food Science and Technology, 2023)